Prediction of Reverberation time in university classrooms using Neural Network - Paularaj, M. P.; Mohd Shukry, Abdul Majid; Sazali, Yaacob; Hariharan, M.; Wan Mohd Ridzuan, Wan Ab Majid (Universiti Kebangsaan Malaysia, 2009)
Organized by Fakulti Kejuruteraan (Universiti Kebangsaan Malaysia), 27th - 28th November 2007 at Universiti Kebangsaan Malaysia, Selangor.